2017
DOI: 10.1089/jop.2016.0132
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Boosted Decision Tree Classification of Endophthalmitis Versus Uveitis and Lymphoma from Aqueous and Vitreous IL-6 and IL-10 Levels

Abstract: With limited sample size, gradient boosting can differentiate endophthalmitis from uveitis and lymphoma by IL-6 and IL-10 with high sensitivity and specificity; however, a larger cohort is needed for further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Malignant B cells often express high levels of IL‐10, while inflammatory cells produce high levels of IL‐6. Therefore, an IL‐10/IL‐6 ratio greater than 1 has high specificity in favour of B‐lymphoma, which was the case for 8/12 of DLBCL patients in our cohort . The dilution of the sample may have contributed to the low positive cytokine outcome (58%) in this cohort, compared to a better rate in the literature (>90% of cases).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Malignant B cells often express high levels of IL‐10, while inflammatory cells produce high levels of IL‐6. Therefore, an IL‐10/IL‐6 ratio greater than 1 has high specificity in favour of B‐lymphoma, which was the case for 8/12 of DLBCL patients in our cohort . The dilution of the sample may have contributed to the low positive cytokine outcome (58%) in this cohort, compared to a better rate in the literature (>90% of cases).…”
Section: Discussionmentioning
confidence: 51%
“…The dilution of the sample may have contributed to the low positive cytokine outcome (58%) in this cohort, compared to a better rate in the literature (>90% of cases). However, IL can be variable in pathological aqueous or vitreous samples, regardless of the pathology, including endophthalmitis, uveitis or lymphoma …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in animal model with endotoxininduced uveitis protective role of local IL-10 was confirmed [59,60]. Сorrelation between level of IL-10 to level of IL-6 allows to determine the diagnosis (uveitis or intraocular tumor) [61,62].…”
Section: Review and Discussionmentioning
confidence: 89%
“…In addition, our previous study showed that rno-miR-30b-5p was upregulated in peripheral blood mononuclear cells in EAU rats; the predicted target genes are related to Becn1, Atg 12 and IL-10, IL21r, and TLR 4, which are involved in autophagy, immune signaling pathways [ 22 ]. It is well known that both IL-10 [ 33 ] and TLR4 [ 34 ] are involved in the development of uveitis. Therefore, we further explored the relationship between the expression levels of rno-miR-30b-5p and IL-10 and TLR4 and the development of uveitis.…”
Section: Discussionmentioning
confidence: 99%